TAREKAT, KESALEHAN RITUAL, SPIRITUAL DAN SOSIAL: PRAKTIK PENGAMALAN TAREKAT SYADZILIYAH DI BANTEN - E. Ova Siti Sofwatul Ummah (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2018)
This study attempts to describe the practice of tarekat Syadziliyyah in Pesantren Cidahu, Pandegang, Banten which encourages the realization of the piety of its followers, ritually, spiritually, and socially. Based on the qualitative approach, through an in-depth interview to the people who is practicing tarekat, consisting of santri, the servants of the ‘pesantren’, the head of the village, as well as senior students who are considered to have considerable influence because of their religious knowledge and wisdom, the result of this study shows that the tarekat which is developed by Abuya Dimyathi, through practicing istighfar, shalawat ummi, kalimah tauhid, do'a, wasilah and rabithah had a positive impact on the ritual, spiritual, and social piety of the santri of pesantren Cidahu. Increasing the discipline and routine of the santri in carrying out the obligatory and sunnah worship, devotion, calmness, and surrender in carrying out and responding to the various life activities became its real pieces of evidence.